The Law Enforcement of Journalism Profession in The Context of Press Freedom - Sri Ayu Astuti (Universitas Muhammadiyah Sidoarjo, 2014)
Law No. 40 of 1999 on Press is a manifestation of respect for the legal protection of press workers . Press in their role contributes to the intellectual level of the nation, through the information submitted in news publications, as well as bringing stipulated by the 1945 Constitution of Republic of Indonesia on freedom of thought and speech as Human Rights. However, in carrying out their journalistic duties, the Press should have responsibilities in the news process, and must not violate the ethics of his profession. Press that violates profession intentionally or unintentionally in the writing and publication of news in the public sphere, will still do the law enforcement process for any misuse of the meaning of freedom of speech and thought that harm others. Enforcement of this law, in line with the revocation of the right of immunity of profession issued by the Constitutional Court, which means the Press as a Professional must do the job with the precautionary principle, not by carelessness due to the trapped arrogance of jobs, and injuring other people's human rights, even doing work profession with not commendable behavior. How To Cite: Astuti, S. (2014). The Law Enforcement of Journalism Profession in The Context of Press Freedom. Rechtsidee, 1(2), 175-190. doi:http://dx.doi.org/10.21070/jihr.v1i2.97